2002
DOI: 10.1039/b210541a
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive vitrifiable chiral dimesogens: photo-thermal modulation of microscopic disordering in helical superstructure and glass-forming properties

Abstract: Thermal, photooptical as well as glass-forming properties of a series of photoresponsive chiral dimesogenic compounds containing cholesterol-azobenzene moieties linked to varying alkyl chain lengths (6-14) are described. All compounds except the dimesogen containing 7 methylene spacers show a cholesteric phase. Selective reflections observed in the cholesteric liquid crystals were found to be blue shifted upon increasing the temperature due to variations in smectic fluctuations. X-Ray diffraction studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…[11,[24][25][26][27][28] Recently, we reported that the mechanism of the helical-pitch shift that is induced by achiral dopants (as well as in dimesogenic compounds) is due to enhancement of smectic A (SmA)-like clusters in the cholesteric phases. [29,30] Our interest in this topic is for the design of thermally stable, light-driven, full-color, erasable recording devices. For this purpose, it is necessary to obtain suitable photoresponsive dopants that allow quick writing and provide thermally stable color images.…”
Section: Introductionmentioning
confidence: 99%
“…[11,[24][25][26][27][28] Recently, we reported that the mechanism of the helical-pitch shift that is induced by achiral dopants (as well as in dimesogenic compounds) is due to enhancement of smectic A (SmA)-like clusters in the cholesteric phases. [29,30] Our interest in this topic is for the design of thermally stable, light-driven, full-color, erasable recording devices. For this purpose, it is necessary to obtain suitable photoresponsive dopants that allow quick writing and provide thermally stable color images.…”
Section: Introductionmentioning
confidence: 99%
“…Spin-cast films are typically annealed above the polymer glass transition temperature (T g ) to remove residual solvent and erase any hydrodynamically induced anisotropy. Recently molecular glasses have been investigated as alternatives to amorphous polymer systems (Mallia and Tamaoki, 2003). These monodisperse systems appear to maintain the desirable photomotions and photoswitching properties, while allowing precise control of molecular architecture and thus material properties (Naito and Miura, 1993).…”
Section: Classes Of Azobenzene Systemsmentioning
confidence: 99%
“…[12,24,30] These domains are understood to be consequences of order parameter fluctuations of cholesteric regions to and from a smectic-like arrangement, which are also termed as cybotactic groups. [31,33,34] XRD patterns of unaligned samples of BCn-CD8 mixtures exhibited two diffraction peaks, at 3.15 and 17.1 corresponding to layer spacing of 28.01 and 5.18 . The broad, large-angle peak is assigned to result from interaction of neighboring parallel molecules and the small-angle peak depicts the smectic domains.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…The relationship between FWHM, of the small-angle peak, and the smectic characteristics of similar systems have been explored earlier. [30,31] Figure 5 shows the effect of alkoxy-chain length on the FWHM of the small-angle XRD peaks of BCn-CD8 mixtures. The FWHM of the small-angle XRD peaks for all BCn-CD8 mixtures were larger than that of pure CD8, although there was a red-shift of the reflectance band in each case when compared to that of pure CD8.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
See 1 more Smart Citation